2012
DOI: 10.1007/s13197-012-0627-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flour particle size and damaged starch on the quality of cookies

Abstract: Two wheat varieties 'C 306' and 'WH 542' were milled to obtain flour fractions of different particle sizes. Various physicochemical parameters such as wet and dry gluten, falling number, solvent retention capacity (SRC), alkaline water retention capacity (AWRC) and damaged starch content of the flour fractions were analyzed. The damaged starch values ranged from 5.14% to 14.79% for different flour fractions and increased significantly with decrease in particle size. AWRC and SRC of the flour fractions also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 7 publications
(9 reference statements)
4
77
1
2
Order By: Relevance
“…However, the relationship between compression force and PSA becomes inversely proportional when other ingredients in addition to flours are added into the products. This most likely occurs due to the ability of smaller particles to absorb more water, increasing compression force as related by Barak et al (2012), Mahasukhonthachat et al (2010) and Petitot et al (2010). This fact can be confirmed through the negative correlation between PSA and WAI.…”
Section: Instrumental Color Analysismentioning
confidence: 71%
See 3 more Smart Citations
“…However, the relationship between compression force and PSA becomes inversely proportional when other ingredients in addition to flours are added into the products. This most likely occurs due to the ability of smaller particles to absorb more water, increasing compression force as related by Barak et al (2012), Mahasukhonthachat et al (2010) and Petitot et al (2010). This fact can be confirmed through the negative correlation between PSA and WAI.…”
Section: Instrumental Color Analysismentioning
confidence: 71%
“…This phenomenon has also been reported in other products. Barak et al (2012) attributed this to an increase in water absorption capacity of the flour with finer particle size, which resulted in a dough stiffness that resulted in harder cookies. Petitot et al (2010) observed a heterogeneous dough in pasta produced from legume flours (split pea and faba bean flour).…”
Section: Water Absorption and Solubility Indices Instant Soup (Is)mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, they have expanded less during baking. Some authors explain the expansion in baking with relation to the hydration properties of flours (Barak et al 2014;Barrera et al 2007), but in this case the differences between cookies cannot be attributed to these changes because no significant differences were found between the hydration properties of the different mixtures (Table 1). Other authors have found a correlation between the higher viscosity of the dough and the less expansion or spread of the cookie (Miller and Hoseney 1997), but in this study we did not find any significant differences between the rheological parameters (G′, G″ and G*) of the dough (Table 3).…”
Section: Cookie Propertiesmentioning
confidence: 98%